Susceptibility MRI captures nigral pathology in patients with parkinsonian syndromes - Lewis, Mechelle M.; Du, Guangwei; Baccon, Jennifer; Snyder, Amanda M.; Murie, Ben; Cooper, Felicia; Stetter, Christy; Kong, Lan; Sica, Christopher; Mailman, Richard B.; Connor, James R.; Huang, Xuemei (Movement disorders, 2018)
ABSTRACT Background: Parkinsonisms are neurodegenerative disorders characterized pathologically by α‐synuclein‐positive (e.g., PD, diffuse Lewy body disease, and MSA) and/or tau‐positive (e.g., PSP, cortical basal degeneration) pathology. Using R2* and quantitative susceptibility mapping, susceptibility changes have been reported in the midbrain of living parkinsonian patients, although the exact underlying pathology of these alterations is unknown. Objective: The current study investigated the pathological correlates of these susceptibility MRI measures. Methods: In vivo MRIs (T1‐ and T2‐weighted, and T2*) and pathology were obtained from 14 subjects enrolled in an NINDS PD Biomarker Program (PDBP). We assessed R2* and quantitative susceptibility mapping values in the SN, semiquantitative α‐synuclein, tau, and iron values, as well as neuronal and glial counts. Data were analyzed using age‐adjusted Spearman correlations. Results: R2* was associated significantly with nigral α‐synuclein (r = 0.746; P = 0.003). Quantitative susceptibility mapping correlated significantly with Perls' (r = 0.758; P = 0.003), but not with other pathological measurements. Neither measurement correlated with tau or glial cell counts (r ≤ 0.11; P ≥ 0.129). Conclusions: Susceptibility MRI measurements capture nigral pathologies associated with parkinsonian syndromes. Whereas quantitative susceptibility mapping is more sensitive to iron, R2* may reflect pathological aspects of the disorders beyond iron such as α‐synuclein. They may be invaluable tools in diagnosing differential parkinsonian syndromes, and tracking in living patients the dynamic changes associated with the pathological progression of these disorders. © 2018 International Parkinson and Movement Disorder Society